Nonsense mutations in the can1 locus of Saccharomyces cerevisiae. - Ono, B I (1983)
Yeast mutants resistant to L-canavanine were selected. All were recessive and fell into the can1 complementation group. Nonsense mutations were identified among them by using a set of different suppressors. Frequencies of UAA, UAG, and presumed UGA mutations were 14.8, 0.8, and 0.4%, respectively. A high incidence of nonsense mutations having discriminatory suppression patterns was characteristic of the locus.